INTERACTIVE TEACHING METHODS IN PRIMARY SCHOOL - Tajbenova Dina Kuanishovna (Web of Journals Publishing, 2025)
The article discusses the features of using interactive teaching methods in primary school. Their importance for the formation of cognitive activity, the development of communication skills and creative abilities of younger schoolchildren is emphasised. Particular attention is paid to the classification of interactive methods: game technologies, group work, discussion forms, project and research activities. Practical examples of the application of these methods in the classroom are provided, and their impact on the personal development of students is revealed
Keywords: Interactive methods, primary school, gaming technologies, project activities, group work, personal development.